2005
DOI: 10.1071/en05025
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic's Interaction with Humic Acid

Abstract: Environmental Context. Arsenic is of significant environmental concern in much of the world because of its contamination of waters, from mining, industry, sewage disposal, and agriculture. The environmental mobility of arsenic is controlled primarily by adsorption onto metal oxides, especially iron. Humic substances (natural organic matter), which are ubiquitous in aquatic and soil environments, may interfere with this adsorption and arsenic mobility may be increased. Thus, even if it is assumed that humic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 39 publications
12
89
0
1
Order By: Relevance
“…Generally accepted concept is that HA and As(V) can not form covalent bond because they are both anions, and indirect association of HA and As(V) through metal bridging is the primary mechanism (Redman et al, 2002;Lin et al, 2004). On the other hand, direct association of HA and As(V) has been reported under high HA concentrations at 1500 mg/L (Warwick et al, 2005). The existence of HA-As(V) complex has been confirmed using equilibrium dialysis method with 100 mg/L HA and explained by ligand exchange with phenolate group in HA (Buschmann et al, 2006).…”
Section: Sers Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally accepted concept is that HA and As(V) can not form covalent bond because they are both anions, and indirect association of HA and As(V) through metal bridging is the primary mechanism (Redman et al, 2002;Lin et al, 2004). On the other hand, direct association of HA and As(V) has been reported under high HA concentrations at 1500 mg/L (Warwick et al, 2005). The existence of HA-As(V) complex has been confirmed using equilibrium dialysis method with 100 mg/L HA and explained by ligand exchange with phenolate group in HA (Buschmann et al, 2006).…”
Section: Sers Studymentioning
confidence: 99%
“…Recently, similar with As(III)-HA complex (Liu and Cai, 2012), direct association of aqueous As(V) and HA has been reported through covalent binding mechanisms (Warwick et al, 2005;Buschmann et al, 2006). Warwick et al (2005) concluded the formation of HA-As(V) complexes is favorable in the pH range 8-10 with 1500 mg/L Aldrich HA and 7.5 mg/L As(V). Using an equilibrium dialysis method, Buschmann et al (2006) suggest that about 10% of As(V) may bound to HA through phenolate functional groups in HA.…”
Section: Introductionmentioning
confidence: 99%
“…This result is within expectation as organic amendment has long been adopted as an effective tool for the remediation of heavy metal/metalloids in soils (Park et al, 2011). Furthermore, the affinity of Cd on organic matter was found stronger than that of As (reflecting on the r 2 values), which is in accordance with the general order of affinity of heavy metal/metalloids on organic matter (Takamatsu et al, 1983;Warwick et al, 2005). Moreover, dissolved organic carbon played a more important role in controlling Cd bioaccessibility (r 2 = 0.61).…”
Section: Relationships Between the Bioaccessibility Total Concentratsupporting
confidence: 72%
“…Aqueous DOM-metal complexes may, in turn, associate strongly with other dissolved anions, presumably by metal-bridging mechanisms (Thanabalasingam and Pickering, 1986;Warwick et al, 2005). A ternary complexation mechanism, in which cationic metals mediated the strong association between DOM functional groups and As oxyacids was proposed as a plausible mechanism to explain aqueous complexing o f DOM with As oxyanions (Lin et al, 2004;Redman et al, 2002), although no solid proof has confirmed this hypothesis.…”
Section: Arsenic Distributionmentioning
confidence: 99%
“…Numerous studies have already been conducted on As adsorption onto oxy-hydroxides (Dzombak, 1990;Gupta and Chen, 1978;Lafferty and Loeppert, 2005;Oscarson et al, 1983;Tossell, 1997;Wilkie and Hering, 1996) and clay minerals (Goldberg, 2002;Goldberg and Glaubig, 1988;Griffin et al, 1977;Manning and Goldberg, 1997). However, only a few of those considered the interactions of As with organic matter (Alberic et al, 2000;CanoAguilera et al, 2005;Grafe et al, 2001;Redman et al, 2002;Thanabalasingam and Pickering, 1986;Warwick et al, 2005) and/or organic-mineral complexes (Saada et al, 2003;Takahashi et al, 1999;Xu et al, 1988), although this has often been revealed as one of the determining factors in cycling o f metallic and metalloid pollutants. Moreover, the possibility o f As adsorption on organic matter in soil has often been reported (Bhumbla and Keefer, 1994;Chen et al, 1994;Lund and Fobian, 1991;Mok and Wai, 1994;Viraraghavan et al, 1992).…”
Section: Introductionmentioning
confidence: 99%